2019 IEEE International Conference on Consumer Electronics (ICCE) 2019
DOI: 10.1109/icce.2019.8661909
|View full text |Cite
|
Sign up to set email alerts
|

Security Implications of Fog Computing on the Internet of Things

Abstract: Recently, the use of IoT devices and sensors has been rapidly increased which also caused data generation (information and logs), bandwidth usage, and related phenomena to be increased. To our best knowledge, a standard definition for the integration of fog computing with IoT is emerging now. This integration will bring many opportunities for the researchers, especially while building cyber-security related solutions. In this study, we surveyed about the integration of fog computing with IoT and its implicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 3 publications
(4 reference statements)
1
19
0
Order By: Relevance
“…In the literature, many attacks have been identified in IoT networks such as Mirai and Torii botnet attacks [ 9 ], and various attacks against industrial networks (IIoT, etc.) such as Stealthy attacks [ 17 ].…”
Section: Fog Vs Cloud/mobile-edge Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, many attacks have been identified in IoT networks such as Mirai and Torii botnet attacks [ 9 ], and various attacks against industrial networks (IIoT, etc.) such as Stealthy attacks [ 17 ].…”
Section: Fog Vs Cloud/mobile-edge Computingmentioning
confidence: 99%
“…As an example, smart cards are used for multiple tasks such as accessing a facility or keeping monetary information, etc. and a simple cloning attack may have an immediate impact [ 9 ]. In the case of cloning being successful for bank cards, the financial loss would be devastating.…”
Section: Hardware Assisted Security Of Fog Computing Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tradeoff between latency, network efficiency, and network size [33] The authors in [34] reviewed the scenarios and security issues of fog computing. In [35], the authors showed a subset of possible attack scenarios from real life applications. They also presented the solutions on each possible attack.…”
Section: Security and Data Privacymentioning
confidence: 99%
“…Thereby, the integration of fog computing will not only remain in just IoT domain, but also expand to IIoT and further other areas. This will impose its own challenges to IIoT, as well as bringing benefits [5]. Especially, cross relations among fog computing devices and underlying IIoT network and communication protocols are the research area of interest.…”
Section: Introductionmentioning
confidence: 99%